The Role of Ozonated Jerusalem Artichoke Ointment on the Healing of Surgically Created Full-Thickness Cutaneous Wounds in Rabbits - Ali Ghazi Atiyah; Mustafa Salah Hasan; Maher Saber Owain (Veterinary Medicine International)
Jerusalem artichoke (J.A.) tubers contain compounds that exhibit anti-inflammatory effects and can minimize tissue damage. Ozone is an alternative antimicrobial and immunomodulatory agent for promoting tissue regeneration. The present study aimed to evaluate the therapeutic effect of the ozonated J.A. ointment on a surgically created full-thickness cutaneous wound in rabbit models. The previously prepared J.A. ointment was ozonated using a Herrmann generator, followed by a subsequent evaluation of its physical and antibacterial properties. Thirty healthy male albino rabbits were used in this study. The animals were divided into two equal groups: the control and treated group. An excisional wound model was used to assess wound healing activities. All of the animals underwent surgical preparation of their dorsal surfaces, and excisional lesions of 3 cm in diameter were created on each animal’s dorsal surface of the thoracolumbar region. In the control group, the wounds were left untreated. The animals in the treatment group received a topical application of ozonated J.A. ointment twice daily for five days following the injury. The animals were euthanized on Days 7, 14, and 21 after the injury for histological evaluation. The agar well diffusion method demonstrated the antimicrobial efficacy of the ozonated J.A. ointment. Also, macroscopic and histopathological results showed a significant (p<0.05) increase in wound area contraction with enhancement re-epithelization in the treated group compared to the control group. In conclusion, the ozonated ointment derived from J.A. tubers has antibacterial properties and can promote and enhance the wound healing process.